(untitled) (Research, Society and Development, 2025)
Human activity in forest environments, mainly for the formation of arable areas, causes environmental impacts in river basins. Thus, the objective of this research was to study the use and occupation of the land of the Alto Juruá river basin located in the State of Acre, over a period of 36 years (1985-2020), in order to identify in which period there was a greater occurrence of human activity in the landscape. Data from the MapBiomas platform, version 3.0, was used, with the aid of Google Earth Engine. The results indicated that agriculture had a greater presence in the period studied and that in 2020 this agent represented 4.8% of the total area of the basin. The pasture class did not show an increase, contributing 0.26% in 2018. The forest formation class, with 94%, indicated that the basin has a large forested area. Finally, the urban infrastructure class was equal to 0.1%. It is concluded that the Alto Juruá river basin presented a certain degree of disturbance mainly due to agriculture to the detriment of other classes such as pasture.